(3CLhHI CHj GdUdJ Yf eSGFd SFd YfgGs - (3CejI Hf YHO GdYRjR GdCfOdSj, CHh GdUdJ,J (B529 (3g` s
(3ChdgG (B:s
(3CLhHI eSGFd SFd YfgG CHh GdUdJ QMeI Gddg cGf bO hQO GdeSFdI GdChdi ai JhMO GdPGJ hai UaGJgG ajecf Cf jage efgG GdSDGd Yf JhMOgG hGdSDGd Yf YOe eZGjQJgG s
(3BNQgG (B:s
(3hadc GdJOhjQ YdhG Ydi gPG GdhLg ebOGQ CHYO CHYGO YWGQO JeJ HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG QShe gfOSjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(646/2) s
Keywords: (3Gdabg GdESdGejs